Field evaluation of a novel semi-quantitative point-of-care diagnostic for G6PD deficiency in Indonesia - Sadhewa, A; Panggalo, LV; Nanine, I; Price, RN; Thriemer, K; Satyagraha, AW; Ley, B (Public Library of Science, 2024)
Background: The WHO recommends routine testing of G6PD activity to guide radical cure in patients with Plasmodium vivax malaria. Females may have intermediate G6PD enzyme activity and to date, only complex diagnostics are able to reliably identify them. The semi-quantitative G6PD diagnostic “One Step G6PD Test” (Humasis, RoK; “RDT”) is a lateral flow assay that can distinguish deficient, intermediate, and normal G6PD status and offers a simpler diagnostic alternative. Methods: G6PD status of participants enrolled in Malinau and Nunukan Regencies and the capital Jakarta was assessed with the RDT, and G6PD activity was measured in duplicate by reference spectrophotometry. The adjusted male median (AMM) of the spectrophotometry measurements was defined as 100% activity; 70% and 30% of the AMM were defined as thresholds for intermediate and deficient G6PD status, respectively. Results were compared to those derived from spectrophotometry at the clinically relevant G6PD activity thresholds of 30% and 70%. Results: Of the 161 participants enrolled, 10 (6.2%) were G6PD deficient and 12 (7.5%) had intermediate G6PD activity by spectrophotometry. At the 30% threshold, the sensitivity of the RDT was 10.0% (95%CI: 0.3–44.5%) with a specificity of 99.3% (95%CI: 96.4–100.0%); the positive predictive value was 50.0% (95%CI: 1.3–98.7%) and the negative predictive value 94.3% (95%CI: 89.5–97.4%). The corresponding figures at the 70% threshold were 22.7% (95%CI: 7.8–45.4%), 100.0% (95%CI: 97.4–100.0%), 100.0% (95%CI: 47.8–100.0%) and 89.1% (95%CI: 83.1–93.5%), respectively. Conclusion: While there is a dire need for an easy-to-use, economical, semi-quantitative diagnostic for the point of care, the observed performance of the “One Step G6PD Test” in its current form was insufficient to guide antimalarial treatment.